Produções textuais na EJA: a reescrita como prática de aprendizagem - Vieira, Ana Maria Marques (2015)
It is known that access to the written language mode is extremely important for the inclusion of individuals in grafocentics societies such as ours, however, we realized that mechanisms used in language teaching today still excludes the student in the teaching and learning process. To contribute with reflections in that field, this work presents the results of a survey that aims to reflect on the use of cohesive elements in the practice of textual production of a group of students belonging to a classroom of Educação de Jovens e Adultos (EJA). The study was conducted with students from ninth grade, fourth cycle of elementary school, belonging to a school municipal of Bayeux, Paraíba. Through this investigative process of qualitative, descriptive and interventionist nature, we promote the progress of these students, with regard to the acquisition of skills related to writing as a reflection on the use of cohesive elements, reviewing and rewriting texts. It was observed that the oral influence is a major reason that leads the student to confuse the use of the service system of written language. In the specific case of this study, the adversative conjunction “but” was misspelled as intensity adverb “more”. In this context, we understand that EJA students communicates and makes use of writing in their daily lives. They are, therefore, literate, however discredited because they don’t dominate the cultured language writing system, especially in relation to use of cohesive elements in the textual output. Considering such problems, we have developed writing activities, reflection and rewritten, emphasizing the importance of the written text area, working the inadequacies in order to provide learning to these students. The intervention proposal developed in the classroom was based on studies and proposals produced by Dolz, Noverraz and Schneuwly on didactic sequences and studies Gasparotto; Menegassi (2012) on the text rewritten. The work was built, taking also as reference studies by theorists such as Antunes (2003), Bagno (2010, 2013), Christiano and Silva (2005), Kleiman (2012), Kleiman and Sepulveda (2012), Koch and Elias (2014 ). Koch (2013) Marcuschi (2010), Neves (1990, 2004, 2010), Perini (2010), Possenti (1996), in addition to the PCNs and the textbook adopted by the school. Students advanced in understanding the idea of being more aware in the production of texts, not only when they are experiencing other levels of education, as well as the daily needs that emanate from the social use of writing practices.